Preparation of fluorine and carbon co-introduced TiO2 at low temperature with enhanced visible-light degradation performance for 2,4,6-trichlorophenol - Yang Tang; Fang Shen; Hao Huang; Hongyan Shang; Hui Mao; Jun Ma; Yang Liao; Shilin Zhao (Materials Research Express, 2020)
Traditional TiO _2 photocatalyst has the disadvantages of weak visible-light responsibility, fast combination of photo-generated electron and hole, which significantly degrade its photocatalytic degradation activity. Therefore, fluorine and carbon co-introduced TiO _2 was synthesized at a relatively low calcination temperature via a modified sol-gel method, and then be thoroughly characterized to explore the structure-performance relationship. It was found the optimum catalyst FCT-200 prepared at calcination temperature of 200 °C exhibited remarkably enhanced visible-light absorption and restrained photo-generated carrier combination, which should be attributed to the F, C elements co-introduction, lower crystallization degree, and smaller particle size of anatase TiO _2 . With such advantages, the catalyst therefore demonstrated satisfactory photocatalytic degradation activity for 2,4,6-trichlorophenol (2,4,6-TCP) under visible-light irradiation. The apparent degradation rate reached as high as 0.41971 h ^−1 , almost 42 folds higher than P25. It is anticipated that the fluorine and carbon co-introduced TiO _2 photocatalyst presented in this work could provide a new insight into significantly improving the photocatalytic performance of TiO _2 .